2014
DOI: 10.1080/00223891.2014.938750
|View full text |Cite
|
Sign up to set email alerts
|

French Validation of the Overexcitability Questionnaire 2: Psychometric Properties and Factorial Structure

Abstract: Overexcitability corresponds to an overall response to stimulations in 5 domains: psychomotor, sensual, intellectual, imaginational, and emotional. The aim of this study was to develop a French version of the Overexcitability Questionnaire 2 (OEQ2) and to expand its psychometric properties. Two studies were conducted: one with a sample of 474 adolescents and another with a sample of 436 adults. Internal consistency, factorial structure, and validity (correlations with intelligence, personality, and alexithymia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 63 publications
2
22
0
1
Order By: Relevance
“…The same correlates were found in the study by Botella et al (2015). The study also showed a number of other weaker relationships: positive relationships between sensual, imaginational and intellectual OE with neuroticism, a negative relationship between sensual OE and extraversion, a positive relationship between emotional OE and openness, positive relationships between psychomotor, sensual and intellectual OE and conscientiousness, a negative relationship between imaginational OE and conscientiousness, positive relationships between sensual and emotional OE and agreeableness, as well as a negative relationship between intellectual OE and agreeableness.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…The same correlates were found in the study by Botella et al (2015). The study also showed a number of other weaker relationships: positive relationships between sensual, imaginational and intellectual OE with neuroticism, a negative relationship between sensual OE and extraversion, a positive relationship between emotional OE and openness, positive relationships between psychomotor, sensual and intellectual OE and conscientiousness, a negative relationship between imaginational OE and conscientiousness, positive relationships between sensual and emotional OE and agreeableness, as well as a negative relationship between intellectual OE and agreeableness.…”
Section: Introductionsupporting
confidence: 89%
“…Finally, our results comply with the outcomes of previous studies which show that the correlates of psychomotor OE differ from other types. For example, in a study by Botella et al (2015), psychomotor OE proved to be the only type of overexcitability to be positively correlated with extraversion (see also Limont, Dreszer & Bedyńska, 2010) and not correlated with openness to experience or alexithymia. Data concerning the positive relationship between this type of OE and self-concept (Gross et al, 2007;Rinn et al, 2010) also agrees with our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A construção e a utilização de instrumentos de SE têm sido alvo de investigações em diferentes países (Al-Onizat, 2013;Almutairi, 2010;Botellaab, Fürstac, Myszkowskiad, Stormead, Costa, & Luminetb, 2015;Rost, Wirthwein, & RSteinmayr, 2014;Siu, 2010;Van den Broeck, Hofmans, Cooremans, & Staels, 2014), sendo que as pesquisas sobre D&T (Chang & Kuo, 2009;Piirto & Fraas, 2012;Tieso, 2007a;) e a associação entre os cinco padrões e o sexo dos respondentes se destacam. No último caso, tem sido observado que pessoas do sexo feminino tendem a exibir médias significativamente mais altas nos padrões Emocional e Sensorial (Al-Onizat, 2013;De Bondt & Petegem, 2015;He & Wong, 2014;Miller, Falk, & Huang, 2009;Siu, 2010;Thomson & Jaque, 2016;Tieso, 2007aTieso, , 2007bTreat, 2006;Van den Broeck et al, 2014;, enquanto o sexo masculino tende a apresentar escores médios mais altos nos padrões Psicomotor e Intelectual (De Bondt & Petegem, 2015;Rinn, Mendaglio, Rudasill, & McQueen, 2010;Tieso, 2007b;Van den Broeck et al, 2014).…”
unclassified